Proyecto de tesis de grado sobre el “desarrollo y automatización del control de asistencia docente y cumplimiento del programa de estudio” para la unidad edcom - Celi Campoverde, Yenny E. (2009)
This project will develop a tool that satisfies the need to control the staffing of the "EDCOM" (School of Visual Communication and Design) in assisting in their chairs and monitoring the curriculum of different Subjects taught. Its importance is based on academic unit that is certified to ISO 9001:2000 requires that the verification of compliance through documentation so that the processes of control and enforcement of Teaching curriculum were initially implemented by hand and that soon became complicated steps to control the number of teachers and Careers Unit. The tool will allow teachers to record their entry and exit classes detailing what is going to deliver in accordance with the sessions of the curriculum, the same will be informed if their attendance is within a "range-time" or is considered a " Missing or delayed ", and it can keep track of sessions delivered or given by the Program for the Study of Matter, will also be used for applications for recovery of their class and approval, in addition to reading news and feedback.